2022
DOI: 10.1111/jasp.12898
|View full text |Cite
|
Sign up to set email alerts
|

Outgroup exclusion, identity, and collective action in the Brexit context

Abstract: This paper explored how the source of exclusion (ingroup/outgroup) influences ingroup identification and political engagement. It is well documented that social exclusion has a negative impact on individuals' well-being, but less is known how it affects identification with the ingroup, and subsequent behavior. In two studies, one survey (N = 193) and one experiment (N = 384), we explore how exclusion in the context of Brexit impacts identification with the EU and Remain cause and in turn engagement with a pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Given that feelings of exclusion were established in the minority, in line with previous research it was likely that minority individuals would try to establish social connections to fortify their threatened fundamental needs as seen in traditional social exclusion research (Williams, 2007(Williams, , 2009. In line with previous empirical studies that have demonstrated the causal role that exclusion has with engagement in political and radical actions, we argued that those in the minority would be more willing to participate in and endorse radical actions (Pfundmair, 2019;Renström et al, 2020;Knapton et al, 2022). Our findings confirmed this.…”
Section: Exclusion and Radicalizationsupporting
confidence: 91%
See 4 more Smart Citations
“…Given that feelings of exclusion were established in the minority, in line with previous research it was likely that minority individuals would try to establish social connections to fortify their threatened fundamental needs as seen in traditional social exclusion research (Williams, 2007(Williams, , 2009. In line with previous empirical studies that have demonstrated the causal role that exclusion has with engagement in political and radical actions, we argued that those in the minority would be more willing to participate in and endorse radical actions (Pfundmair, 2019;Renström et al, 2020;Knapton et al, 2022). Our findings confirmed this.…”
Section: Exclusion and Radicalizationsupporting
confidence: 91%
“…Belonging to a group can restore significance and recent research show that loss of significance increases subsequent extreme group identification (Bäck et al, 2018a;Renström et al, 2020). Recent studies also show that the link between significance loss and radicalization is mediated by identification with the ingroup (Knapton et al, 2022;Milla et al, 2022).…”
Section: Radicalization and Social Exclusionmentioning
confidence: 99%
See 3 more Smart Citations